CE marking as a necessary requirement of free marketing and use of medical products - Borek-Wojciechowska, Regina; Kłokow, Sylwia (Polish Journal of Public Health, 2009)
Introduction of the New and Global Approach to the European Union has considerably changed the attitude to safety of industrial products as well. A new concept of conformity assessment has been adopted, and the compliance with requirements of the New Approach technical directives has been expressed in the CE marking. CE marking is obligatory. Failure to comply with the solutions relating to CE marking results in sanctions, also economic. CE marking and all the associated consequences are applicable to marketing and use of medical products, except for medical products made to order, for clinical trials, and medical products for evaluating performance of in vitro diagnostics. The issue of marketing and use of medical products and procedures of CE marking applied to medical products are discussed in the present paper.